Zakat Intermediaries and Its Impact to Industry Growth: Growth Accelerators or Cost Center? - Taufik Syamlan, Yaser; Riyanto, Hadi; Asfia, Asfa (International Journal of Islamic Economics and Finance (IJIEF), 2021)
This study aims to determine the effect of Islamic bank’s activity as a zakat intermediator on profitability, efficiency, market share, and growth of Islamic banks in Indonesia. This research also analyses from the literature the possibility of zakat as the funding or financing product. The method used is the panel data method and granger causality. The Independent variable external zakat collection while the dependent variables are ROA, BOPO, Market Share, and Growth. The samples of the research are five Islamic Bank who has done the external zakat collection. The data used are quarterly data with a period from 2013 to 2020. The results of this study indicate that this divine role increase the cost of operation and in the same time decreasing the profitability. The result also stated that the intermediating activities of zakat collection is not significant to push the bank market share, profitability as well as the Bank Growth. However, although in terms of regulation bank cannot be the Amil, in the future, there is potential of zakat can push the Islamic market share and bank growth since the zakat collection, Islamic bank can offer third party funding product as the intermediation between the zakat payer and the Amil zakat whose eligible to collect zakat according to the government regulation.